Polyphenol Contents, Antioxidant and Anticancer Activity (MCF-7) of Soybean Products in Thailand - Thidarat Somdee (Science Faculty of Chiang Mai University, 2019)
This investigation aimed to assess the phytochemical properties of processed soybeans (steamed soybean, soymilk and tofu) from three Thai cultivars, which included the total phenol content (TPC), total flavonoid content (TFC), 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant potential (FRAP) and β- carotene bleaching activity, the anti-carcinogenic property in the MCF-7 cell line and genistin content were also measured. The three Thai soybean cultivars were Chiang Mai 6 (CM6), Chiang Mai 60 (CM60) and new cultivar Chiang Mai 84-2 (CM 84-2). The levels of TPC and TFC were in the ranges of 60.02 - 70.47 mg GAE/100g dry weight and 21.90 - 39.84 mg CE/100g dry weight, respectively. The tofu produced from all cultivars exhibited significantly higher antioxidant activity in the DPPH assay than the other products. The soymilk of all cultivars had the greatest FRAP values, while 3 products of CM 84-2 had the highest percentage inhibition in the β- carotene bleaching assay regardless of the soybean product type. Moreover, almost soybean products showed low anticancer activity, which was more significant in tofu and steamed soybean CM6 samples and inactive in tofu from CM 60 and CM 84-2. The genistin levels in soybean products were estimated to be between 3.43 and 32.02 µg/g. Therefore, the phytochemical properties of soybean depended upon the different Thai cultivars and type of postharvest processing.